Chromatographic characterisation of aptamer-modified poly(EDMA-co-GMA) monolithic disk format for protein binding and separation - Acquah, C.; Danquah, M.; Chan, Y.; Loo Chin Moy, Charles; Ongkudon, C.; Lau, John (Taylor & Francis Inc., 2018)
The introduction of aptameric ligands onto disk-monolithic adsorbent, representing a unique strategy for convective isolation of target molecules with high specificity and selectivity, is investigated for the first time. Experimental results showed that the disk monolith possessed a good permeability of 1.67 ± 0.05 × 10 –14  m 2 (RSD = 3.2%). The aptameric ligand density for the aptamer-modified disk monolith was 480 pmol/uL. Chromatographic analysis of the aptamer disk-monolith efficiency showed an optimum linear velocity of 126 cm/min (˜0.25 mL/min) at room temperatures 25 ± 2°C. The theoretical number of plates corresponding to the optimum linear velocity was 128.2 with an height equivalent to the theoretical plate of 0.022 mm. The disk aptamer-immobilised monolithic system demonstrated good selectivity and isolation of thrombin from non-targets.